SELF CONTROL DALAM MENEKAN PERILAKU SOCIAL ANXIETY PADA REMAJA - IQBAL BAFADAL (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2021)
Developmental tasks are one of the requirements that must be met to achieve maturity in adolescents both in cognitive, affective, and psychomotor aspects. However, the emergence of anxiety in adolescents as the introductory stimulus to negative behaviours becomes an obstacle in achieving these developmental tasks. This study aims to reveal how self-control plays a role in suppressing aspects of anxiety that exist in adolescents through treatment in the form of training. This study uses a quantitative approach with experimental methods. The design and test of data analysis used paired statistical test of sample t-test on the pre-test and post-test of the experimental group and the control group. Respondents in this study amounted to 24 teenagers. Measurements were made through a psychological scale instrument on the aspect of anxiety. Based on statistical tests, it was found that the conditions for H0 were rejected and H1 was accepted, which means that there is a difference in anxiety in adolescents before and after treatment or self-control training.